2022
DOI: 10.1007/s00170-022-10398-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the mechanical properties of 3D printed hybrid continuous fiber-filled composite considering influence of interfaces

Abstract: Fused deposition modeling (FDM) is a promising additive manufacturing technique for fabrication of continuous fiber-reinforced thermoplastic composites. For composite applications, the balance of material properties, including rigidity and toughness, needs to be considered. To overcome the drawbacks induced by single continuous fiber reinforcement, this study focused on the design and characterization of hybrid continuous fiber (continuous carbon and Kevlar fibers)-reinforced polyamide (PA)-based composites, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…It is also recommended to follow up on study C, which suggests a high combination potential of WPC with PCM. There are also applications of additive 3D printing of FRP [46,47]. Future research should investigate synergies with thermoforming technology.…”
Section: Discussionmentioning
confidence: 99%
“…It is also recommended to follow up on study C, which suggests a high combination potential of WPC with PCM. There are also applications of additive 3D printing of FRP [46,47]. Future research should investigate synergies with thermoforming technology.…”
Section: Discussionmentioning
confidence: 99%
“…The processes of compounding and FDM printing helped in the void reduction and the nonformation of agglomerates, leading to an enhanced ultimate tensile strength [34]. The enhanced mechanical strength of the BN-reinforced composites was also due to the alleviated contact surface area between the matrix and filler, which permitted the load to be effectively transferred to the BN network [35]. The process of building a part through an infill pattern also played an important role in determining the strength of the parts.…”
Section: Ultimate Tensile Strengthmentioning
confidence: 99%
“…Many researchers have investigated the mechanical behaviour of continuous fibre-reinforced 3D-printed specimens [ 20 , 21 , 22 , 23 , 24 , 25 ], with the majority focusing on tensile behaviour. Li et al [ 24 ] investigated hybrid (carbon and Kevlar) continuous fibre-reinforced polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have investigated the mechanical behaviour of continuous fibre-reinforced 3D-printed specimens [ 20 , 21 , 22 , 23 , 24 , 25 ], with the majority focusing on tensile behaviour. Li et al [ 24 ] investigated hybrid (carbon and Kevlar) continuous fibre-reinforced polymer. They found that an infill ±45° to the loading direction resulted in the lowest modulus and strength, followed by a 90° infill, with an infill parallel to the loading direction yielding the strongest parts with the highest modulus.…”
Section: Introductionmentioning
confidence: 99%